Modified atmosphere together with refrigeration in the conservation of bananas resistant to black Sigatoka - Siqueira, Célia; Almeida, Hilário; Serpa, Miryan Franciele; Batista, Paulo Sérgio; Mizobutsi, Gisele (Revista Ciência Agronômica, 2017)
The aim of this work was to evaluate the chemical, physical and sensory characteristics of the Caipira and Pakovan Ken cultivars of the banana (Musa spp.), resistant to black Sigatoka (Mycosphaerella fijiensis Morelet), both with and without low-density polyethylene wrapping and together with refrigeration during the period of post-harvest storage. The experiment was carried out in 2012, in a randomised block design and an arrangement of lots split over time. A 3 x 2 factorial scheme was used for the lots, consisting of fruit with no wrapping and fruit wrapped in 10 and 16 μm polyethylene film, and two cultivars, Caipira and Pakovan Ken. The sub-lots consisted of evaluations made at intervals of six days (0, 6, 12, 18 and 24) and of two days (0, 2, 4, 6 and 8), for fruit stored at temperatures of 12, 15 and 25 °C respectively. The following variables were evaluated: soluble solids, titratable acidity, ratio of soluble solids to titratable acidity, hydrogen potential, total soluble sugars, fruit colouration and sensory analysis. The polyethylene film together with the refrigeration enabled the fruit to be stored for 24 days, maintaining post-harvest characteristics suitable for consumption. The Pakovan Ken cultivar stood out when compared to the Caipira, with higher values for the fruit attributes under evaluation.